Clinical observations on super relaxation suture in the resection of benign skin tumor in children - Ling Chen; Huiming Zhang; Yi Zhan; Yu Zeng; Siqi Fu (Journal of Dermatological Treatment)
Background and Objective This study compares the clinical effectiveness of super relaxation suture technique using barbed polydioxanone suture (PDS) with in-situ return needle horizontal mattress suture against conventional subcutaneous heart-shaped suture technique in resecting benign skin tumors in children.Methods 40 children with benign skin tumors who underwent outpatient surgery and received super relaxation suture were assigned to the observation group. The control group comprised 24 children treated with conventional subcutaneous heart-shaped suture technique after the resection of benign skin tumors. The postoperative scars of the two patient groups were evaluated.Results After a postoperative follow-up period of 3–24 months, 38 out of the 40 patients in the observation group exhibited linear wound scars, while 2 patients presented with hyperplastic scars on their chests. In the control group comprising of 24 patients, one patient had depression scar on face, two patients displayed noticeable hyperplastic scars on scalps, and one patient developed keloid on lower limb.Conclusion Super relaxation suture technique using PDS in situ backstitch horizontal mattress suture is more effective than conventional subcutaneous heart-shaped suture technique in reducing tension post-benign skin tumor resection in children, promoting wound healing, and minimizing scar formation.